2000
DOI: 10.1103/physrevlett.85.2681
|View full text |Cite
|
Sign up to set email alerts
|

Antideuteron Production in158AGeV/cPb+PbCollisions

Abstract: The invariant cross section as a function of transverse momentum for antideuterons produced in 158A GeV͞c per nucleon Pb 1 Pb central collisions has been measured by the NA44 experiment at CERN. This measurement, together with a measurement of antiprotons, allows for the determination of the antideuteron coalescence parameter. The extracted coalescence radius is found to agree with the deuteron coalescence radius and radii determined from two particle correlations. PACS numbers: 25.75.Dw, 14.20.Dh, 25.40.Ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…In the year 2000, the Brookhaven E864 collaboration [152,154] plotted points include data from NA52 [150,151], NA44 [153] and E864 [152,154]. The E864 collaboration [152] concluded that these measurements favor the picture of Scheibl and Heinz [148] in which B 2 and B 2 are about equal, and disfavor the alternative picture where B 2 is smaller [145,146,147].…”
Section: Yields Of Antinuclei In Heavy-ion Collisions At the Ags And Spsmentioning
confidence: 99%
“…In the year 2000, the Brookhaven E864 collaboration [152,154] plotted points include data from NA52 [150,151], NA44 [153] and E864 [152,154]. The E864 collaboration [152] concluded that these measurements favor the picture of Scheibl and Heinz [148] in which B 2 and B 2 are about equal, and disfavor the alternative picture where B 2 is smaller [145,146,147].…”
Section: Yields Of Antinuclei In Heavy-ion Collisions At the Ags And Spsmentioning
confidence: 99%
“…In the AGS 2 Advances in High Energy Physics experiments, it was found that the coalescence parameter ( 2 ) is of similar magnitude for both and indicating similar freeze-out hypersurface of nucleons and antinucleons. Furthermore, the dependence of 2 on collision energy and indicated that light nuclei production is strongly influenced by the source volume and transverse expansion profile of the system [58,59]. In this paper, we review the results of elliptic flow of light nuclei measured at RHIC and LHC and discuss the possible mechanisms for the light nuclei production.…”
Section: Introductionmentioning
confidence: 99%
“…The production of light (anti)nuclei has been studied extensively at lower energies in Bevelac at LBNL [24,[46][47][48][49], AGS at RHIC [50][51][52][53], and SPS at CERN [54][55][56][57][58]. In the AGS 2 Advances in High Energy Physics experiments, it was found that the coalescence parameter ( 2 ) is of similar magnitude for both and indicating similar freeze-out hypersurface of nucleons and antinucleons.…”
Section: Introductionmentioning
confidence: 99%
“…In the coalescence model, nuclei are formed by protons and neutrons which are nearby in space and exhibit similar velocities [5,6]. A quantitative description of this process, applied to many collision systems at various energies [7][8][9][10][11][12][13][14], is typically based on the coalescence parameter B A (see Section 3 …”
Section: Introductionmentioning
confidence: 99%